The Changing Spectrum of Cutaneous Manifestations in HIV Infection: Pre-ART Vs Post-ART Comparative Study - Dr Nancy Garg; Dr Rajendra Devanda; Dr Khushboo Gupta; Dr Khushboo Gupta; Dr U.S Agarwal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Cutaneous manifestations are common in HIV-infected individuals and often reflect the degree of immunosuppression. The introduction of antiretroviral therapy (ART) has significantly altered the natural course of HIV, including its dermatological manifestations. Objective: To analyze the changing profile of cutaneous manifestations in HIV patients before and after the advent of ART. Methods: A comparative observational analysis of 80 HIV-positive patients (40 pre-ART era and 40 post-ART era) was conducted. Data on demographics, CD4 counts, and dermatological conditions were collected and compared. Results: Infectious dermatoses (bacterial, fungal, viral) were more prevalent in the pre-ART group (72.5% vs. 42.5%, p < 0.05), while inflammatory and ART-related dermatoses were more common in the post-ART group (35% vs. 12.5%, p < 0.05). Mean CD4 count was significantly higher in the post-ART group (312 cells/µL vs. 158 cells/µL, p < 0.001). Conclusion: The spectrum of HIV-associated cutaneous manifestations has shifted from predominantly infectious to more non-infectious and ART-related dermatoses following the widespread use of ART.